Peptide radio receptor therapy: The huff and puff strategy of neuroendocrine disease management. (August 2021) - Bodei, Lisa; Kidd, Mark; Modlin, Irvin
Abstract: The recent development of peptide receptor radionuclide therapy (PRRT) into an accepted treatment allows for consideration of the requirements to move beyond the mere concept of tumor therapy. This chapter addresses the limitations of the "huff and puff" theory of tumor destruction by critically applying the knowledge of radionuclide therapy.